2017
DOI: 10.5435/jaaos-d-15-00402
|View full text |Cite
|
Sign up to set email alerts
|

Acute Wound Complications After Total Knee Arthroplasty: Prevention and Management

Abstract: Normal wound healing with avoidance of early wound complications is critical to the success of total knee arthroplasty. The severity of acute complications includes less morbid problems, such as quickly resolved drainage and small superficial eschars, to persistent drainage and full-thickness tissue necrosis, which may require advanced soft-tissue coverage. To achieve proper healing, surgeons must respond to persistent drainage by addressing modifiable patient risk factors, using meticulous surgical technique,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
1
35

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 45 publications
1
40
1
35
Order By: Relevance
“…The presence of peripheral vascular disease has been identified as a risk factor for deep infection, 76 wound healing problems 111 and catastrophic arterial injury after TKA. 112 The evidence for the management of peripheral vascular disease pre-operatively is limited.…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%
“…The presence of peripheral vascular disease has been identified as a risk factor for deep infection, 76 wound healing problems 111 and catastrophic arterial injury after TKA. 112 The evidence for the management of peripheral vascular disease pre-operatively is limited.…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%
“…One of the most feared and di cult to treat complications is periprosthetic infection, which occurs in approximately 1 to 2% of cases, according to recent studies [2,3]. One of the causal factors of prosthesis infection and the poor postoperative evolution of patients is complications related to wound healing [4,5]. Adelani et al showed that patients re-admitted to the hospital after arthroplasty due to non-infectious wound complications had worst knee function and more pain [6].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15]18] Yara iyileşmesini olumsuz yönde etkileyerek, yara sorunlarına yol açan etkenler olarak inflamatuvar hastalıklar, obezite, diabetes mellitus, tütün ürünleri kullanımı, kronik ilaç kullanımı (biyolojik ajanlar, immünsupresif ajanlar, steroid, yüksek doz non-steroid anti-inflamatuvar), bölgesel cilt sorunları (eski insizyon skarları, yanık sekeli, radyasyon uygulanması), periferik vasküler hastalıklar, malnütrisyon, 3,5 gr/dL altında albümin düzeyi, 1500/mL altında lenfosit sayısı, transferrin düzeyinin 200 mg/dL'nin altında olması, hemoglobin değerinin 10 g/dL düzeyinin altında olması sayılabilir (Tablo 2). [15,[18][19][20][21][22] Primer TDA sonrası yara iyileşme sorunları çok sık görülmese de, oluştuğu durumlarda yıkıcı sonuçlara yol açabilir. [19] Yara sorunları ameliyat öncesi iyi bir planlama, hastaya ait risk faktörlerinin modifiye edilmesi, cilt insizyonunun çok dikkatli ve uygun yapılması, yumuşak dokuya saygılı cerrahi uygulanması gibi bazı önlemler ile sıklıkla önlenebilir.…”
unclassified
“…[19] Tablo 2'de belirtilen albümin, transferrin, hemoglobin ve lenfosit değerlerinin normal sınırlarda tutulması ya da optimum hale getirilmesi amacı ile cerrahi öncesinde belirli bir süre anemi tedavisi, nütrisyonun kontrolü, düzenlenmesi ve desteği çok önem arz etmektedir. [18,19,21,23,24] Diyabetik hastalarda hiperglisemi kollajen sentezinde yavaşlama ve yara direncinde azalmaya neden olurken enfeksiyona da eğilimi arttırır. [18,25] Hastaların açlık kan şekeri düzeyinin ameliyat dönemi dönemde 200 mg/dL'nin altında tutulması, ameliyat öncesi HbA1c düzeyinin 6,5'in altında olması muhtemel yara yeri sorunlarını azaltacaktır.…”
unclassified
See 1 more Smart Citation